2014
DOI: 10.3126/jcmc.v4i1.10845
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries among public school children in the Eastern Nepal

Abstract: Aim: To assess the prevalence of dental caries among public school children of eastern Nepal using DMFT and dft index. Methods: Six hundred and sixty six school children were examined for decayed missing and filled teeth. Decayed, Missing and Filled Teeth (DMFT), decayed and filled teeth (dft) and prevalence were calculated. Results: The mean decayed and filled teeth were 1.82 whereas mean Decayed, Missing and Filled Teeth were 0.37.The prevalence of dental caries were 60.3% and 55.6% in the primary and perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
2
13
2
2
Order By: Relevance
“…Similar findings were seen by Rai B, 13 Mishra FM 14 and Mosha HJ 15 who in their studies also reported increased caries prevalence for females. The results of the present study were not in agreement with the study done by Sudha P, Bhasin S and Anegundi RT 16 as they reported increased prevalence of dental caries for males. Also the study conducted by Gathecha G et al 17 revealed that the difference in prevalence of dental caries between boys and girls was not significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were seen by Rai B, 13 Mishra FM 14 and Mosha HJ 15 who in their studies also reported increased caries prevalence for females. The results of the present study were not in agreement with the study done by Sudha P, Bhasin S and Anegundi RT 16 as they reported increased prevalence of dental caries for males. Also the study conducted by Gathecha G et al 17 revealed that the difference in prevalence of dental caries between boys and girls was not significant.…”
Section: Discussioncontrasting
confidence: 99%
“…5 The prevalence of dental caries was found to be higher in deciduous and lower in permanent dentition which is similar to other studies. 9,12 This could be due to increased awareness of oral hygiene with increasing age and greater resistant property of permanent teeth to caries process than the primary teeth. 13 But this finding is in contrast to another study.…”
Section: Jcms Nepal 2017;13(2):275-8 Prevalence Of Dental Caries Amonmentioning
confidence: 99%
“…Hal-hal yang dapat diupayakan untuk mencegah karies bertambah parah pada usia ini adalah dengan melakukan tindakan pencegahan primer specific protection berupa aplikasi topikal fluor dan atau pit and fissure sealant pada gigi permanen muda yang dapat dilakukan oleh tenaga profesional kesehatan gigi. [5][6][7][8][9][10] Berbeda dengan gigi permanen, maka pada gigi sulung karies paling banyak ditemukan pada permukaan mesial, diikuti oleh permukaan distal, atau dengan kata lain permukaan proksimal lebih banyak mengalami kerusakan dibandingkan dengan permukaan oklusal pada gigi sulung. Hal ini berhubungan dengan faktor diet dan kebersihan mulut.…”
Section: Hasilunclassified
“…Hal ini sejalan dengan penelitian yang dilakukan oleh Bhagat dan Shresta (2014) 10 , yang mendapatkan prevalensi karies pada anak sekolah di Nepal juga tinggi. WHO menyebutkan bahwa pada 32% anak berusia 12 tahun, atau pada usia akhir periode gigi campuran, ditemukan 3 atau lebih gigi yang berlubang, sedangkan pada anak-anak dan orang dewasa terdapat karies gigi antara 60-90%.…”
unclassified